Historical sketch and current state of weed diversity in continental zone of Ukraine - Fedoniuk, Tetiana; Zhuravel, Serhiy; Kravchuk, Mykola; Pazych, Viktor; Bezvershuck, Ihor (Agriculture and Natural Resources, 2024)
Importance of the work: Over the past 50 years, changes in land use strategies from extensive to intensive, changes in landscape structure and increased agricultural production have had a substantial impact on weed diversity and the ratio of individual weed species in agroecosystems. Objective: To determine the quantitative and qualitative changes in the species composition of weeds in the agrophytocenoses of the continental part of Ukraine and to determine the reasons for these changes based on a retrospective analysis and assessment of the current state in agricultural fields. Such information is necessary to better understand the trends in the expansion of certain species to predict and therefore counteract their expansion. Materials and Methods: Dynamic data were analyzed based on scientific studies carried out in the eastern portion of the continental zone according to European biogeographical zoning. Data were collected on weed from 1975 to 2023 from the systematic records that had been kept during this time for a variety of investigations. Results: Based on the findings, spanning from 1975 to the present, over 700 different species of weeds were identified from Ukraine’s major crop areas. Only about 30 of the recorded species were primary weeds that substantially reduced crop yields; these species were identified in nearly all agrophytocenoses and uncultivated lands in this biogeographic zone, while the remaining 75–225 species could cause minor harm to pastures, hayfields, perennial crops and agricultural crops. Main finding: Even though weed species have changed over time, a few species have dominated all crop types: Cirsium arvense (L.) Scop.; Elymus repens (L.) Gould; Convolvulus arvensis L.; Sonchus arvensis L.; Stellaria media; Chenopodium album; Polygonum aviculare; Galium aparine; and Amaranthus retroflexus. In the continental part of Ukraine, several species were either rare or extinct and not found in any of the plots in the current investigation: Hyoscyamus niger L.; Knautia arvensis L. Coult.; Sherardia arvensis L.; Anthemis arvensis L. and Scleranthus annuus L.